Does a History of Slipped Capital Femoral Epiphysis in Patients Undergoing Femoroacetabular Osteoplasty for Femoroacetabular Impingement Affect Outcomes Scores or Risk of Reoperation?. Issue 5 (May 2021) - Sutton, Ryan; Yacovelli, Steven; Vahedi, Hamed; Parvizi, Javad
Abstract: Background: Femoroacetabular impingement (FAI) can occur after slipped capital femoral epiphysis (SCFE) regardless of slip severity and even after in situ pinning. These patients represent a rare and unique demographic that is largely unreported on. It is important to further characterize the clinical presentation of these patients, associated treatment modalities, and the efficacy of these treatment modalities. Questions/purposes: (1) How do patients with post-SCFE FAI typically present in terms of radiographic and surgical findings? (2) How do their hip-specific and general-health outcomes scores after mini-open femoroacetabular osteoplasty compare with those obtained in a matched group of patients with FAI caused by other etiologies? (3) How do those groups compare in terms of the proportion who undergo conversion to THA? Methods: Between 2013 and 2017, 20 patients had femoroacetabular osteoplasty for post-SCFE FAI. During that time, general indications for this procedure were symptomatic FAI demonstrated on radiographs and physical exam. Of those, none was lost to follow-up before a minimum of 2 years, leaving all 20 available for matching, and all 20 had suitable matches in our database for patients who underwent femoroacetabular osteoplasty for other diagnoses. Matching was performed by surgeon, patient age, patient gender, and BMI. The matching group was drawn from a large database of patients who had the same procedure during the same period. We matched in a 1:3 ratio to arrive at 60 randomly selected control patients in this retrospective, comparative study. Patient demographics, medical history, clinical presentation, radiographic parameters, and intraoperative findings were compared between the two groups. At a minimum of 2 years of follow-up, the latest clinical functional outcome scores (Hip Disability and Osteoarthritis Outcome Score Jr and SF-12) and proportions of conversion to THA were compared between the groups. Results: A greater percentage of patients with a history of SCFE than those without prior SCFE demonstrated full chondral lesions intraoperatively (90% [18 of 20] versus 32% [19 of 60], odds ratio 7 [95% confidence interval 1 to 178]; p < 0.01). A greater percentage of patients with a history of SCFE also demonstrated labral calcifications intraoperatively compared with those without prior SCFE (65% [13 of 20] versus 35% [21 of 60], OR 3 [95% CI 1 to 10]; p = 0.04). Radiographically, patients with SCFE had greater preoperative alpha angles than did patients without SCFE (94° ± 13° versus 72° ± 22°; p = 0.01) as well as lower lateral center-edge angles (25° ± 8° versus 31° ± 8°; p = 0.04). There was no difference in postoperative follow-up between patients with a history of SCFE and patients without a history of SCFE (4 ± 2 years versus 4 ± 2 years; p = 0.32). There was no difference in the mean postoperative outcome scores between patients with a history of SCFE and patients without (Hip Disability and Osteoarthritis Outcome Score Jr: 75 ± 28 points versus 74 ± 17 points; p = 0.95; SF-12 physical score: 40 ± 11 points versus 39 ± 8 points; p = 0.79). There was no difference with the numbers available in the percentage of patients who underwent conversion to THA (15% [3 of 20] versus 12% [7 of 60], OR 1.36 [95% CI 0 to 6]; p = 0.71). Conclusion: Patients with FAI after SCFE present with a greater degree of labral and chondral disease than do patients without a history of SCFE. However, at short-term follow-up, the proportion of patients who underwent conversion to THA and patients' postoperative outcome scores did not differ in this small, comparative series between patients with and without SCFE. Further evaluation with long-term follow-up is needed, especially given the more severe chondral damage we observed in patients with SCFE at the time of surgery. Level of Evidence: Level III, therapeutic study.